Absorption mechanism of three curcumin constituents through in situ intestinal perfusion method - Wang,Y.-H. (2017)
This study aimed to investigate the absorption mechanism of three curcumin constituents in rat small intestines. Self-emulsification was used to solubilize the three curcumin constituents, and the rat in situ intestinal perfusion method was used to study factors on drug absorption, including drug mass concentration, absorption site, and the different types and concentrations of absorption inhibitors. Within the scope of experimental concentrations, three curcumin constituents were absorbed in rat small intestines through the active transport mechanism.